1983
DOI: 10.1093/geronj/38.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Acuity in a Healthy Elderly Population: Effects on Emotional, Cognitive, and Social Status

Abstract: Hearing acuity and the relationships between untreated hearing deficits and emotional state, cognitive functioning, and social integration were examined in 239 physically healthy, independent-living elderly men and women with a mean age of 72 years. Air-conduction, pure-tone thresholds in both ears were determined at high- and mid-frequencies, and participants were also given the Speech Perception in Noise test. Multivariate techniques were used to test for associations between hearing acuity and scores from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
2
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 0 publications
7
57
2
1
Order By: Relevance
“…However, this finding has not been universal, nor is sensory deficit necessarily associated with a decrease in social interaction (Norris & Cunningham, 1981;Thomas et al 1983). As Thomas (1981) pointed out, the vast majority of individuals with acquired sensory deficits do not develop psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding has not been universal, nor is sensory deficit necessarily associated with a decrease in social interaction (Norris & Cunningham, 1981;Thomas et al 1983). As Thomas (1981) pointed out, the vast majority of individuals with acquired sensory deficits do not develop psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…This also applies for this present thesis. Numerous studies have shown that there is a correlation between HL and cognitive decline in old age (Granick, Kleban, & Weiss, 1976;Thomas, Hunt, Garry, Hood, Goodwin, & Goodwin, 1983;Lindenberger & Baltes, 1994;Baltes & Lindenberger, 1997;Li & Lindenberger, 2002;Rönnberg et al, 2011), which will be presented more specifically in a subsequent section.…”
Section: Hearing Loss Cognition and Agingmentioning
confidence: 99%
“…These effects have been shown with the Modified Mini-Mental State test (Teng & Chui, 1987), which is a verbal cognitive test, as well as with a non-verbal cognitive test (called Digit Symbol Substitution, Wechsler, 1981), in both cross-sectional and prospective studies (Valentijn et al, 2005;Peters, Potter, & Scholer, 1988). Specifically, verbal tests have shown the relationship between HL and cognitive decline more extensively than non-verbal tests (Granick et al, 1976;Thomas et al, 1983).…”
Section: Cognitive Consequences Of Hlmentioning
confidence: 99%
“…L'altération de la vue est source de chutes et de détérioration de la qualité de vie [6]. De même, l'impact social, cognitif et fonctionnel d'un trouble auditif a été démontré à de multiples reprises [24]. Toutefois, les patients en informent rarement spontanément leur cancé-rologue.…”
Section: Fonctions Sensoriellesunclassified